Family Behaviour In The Prevention of Pulmonary Tuberculosis Transmission Among Children - Tri Makmur; Fazidah Aguslina Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Introduction: Tuberculosis (TB) remains a critical public health priority in Indonesia, with household contacts of patients, particularly children, constituting a high-risk group for infection. The family unit plays a pivotal yet complex role in either mitigating or facilitating transmission within domestic settings. Objective: This study aimed to compare the knowledge, attitudes, and preventive practices (KAP) related to TB between families with and without household TB contacts in Medan, Indonesia. Methods: A comparative cross-sectional study was conducted across eight public health centers in Medan. A total of 100 family respondents (50 with child household TB contacts and 50 without) were recruited. Data on sociodemographics and TB-related KAP were collected via a validated, structured questionnaire and analyzed using Chi-square tests in SPSS 22.0. Results: A stark, inverse distribution was observed. Families with household TB contacts demonstrated significantly poorer knowledge (94.0% poor vs. 6.0% good), less positive attitudes (66.0% good vs. 86.0% good), and markedly inferior preventive practices (12.0% good vs. 93.0% good) compared to families without contacts (p=0.027, p=0.019, and p=0.007, respectively). Conclusions: The study reveals a critical paradox: families at the highest risk of transmission possess the lowest KAP levels for prevention. This indicates a profound failure of current TB contact investigation and education paradigms to effectively penetrate high-risk households. Urgent recalibration of national TB control strategies is needed to implement intensive, household-centered behavioral interventions to break the chain of intra-familial transmission.Keywords: Tuberculosis; Knowledge, Attitudes, Practice; Household Contacts; Health Education; Indonesia.